INNOVATIVE TECHNOLOGIES IN TEACHING FOREIGN LANGUAGES (Innovative Technologica: Methodical Research Journal, 2022)
The article deals with innovative technology that reflects the specifics of the subject under study and the learning environment itself: openness, consistency and consistency, interactivity, visibility of the presentation of the material, multidimensionality and redundancy of all components of the environment. Thus, innovative technology significantly enriches and diversifies the teaching of foreign languages. Monotonous work is being replaced by intellectual creative search.